PROBLEMATIKA HERMENEUTIKA SEBAGAI METODE TAFSIR AL-QUR’AN - Muslim, Ahmad Shobiri (IAIN Kediri, 2015)
Hermeneutics is one of the popular subjects in the world, especially in Indonesia. The subject of hermeneutics isÃ‚Â taught in Islamic universities in Indonesia, particularly in the faculty of Ushuluddin. This paper will examineÃ‚Â hermeneutics as a method of QurÃ¢â‚¬â„¢anic interpretation. It argues that hermeneutics is in fact based on negativeÃ‚Â assumptions about sacred texts, leading to the desacralization of the texts as well as the relativism of religiousÃ‚Â truth. This paper found that hermeneutics is relevant only as a method of biblical interpretation. There areÃ‚Â problems when it is applied to the QurÃ¢â‚¬â„¢anic interpretation because Tafsir and Hermeneutics are two differentÃ‚Â methods.Keywords: Hermeneutika, Teks Suci, Tafsir